“What” and “Where” in Auditory Sensory Processing: A High-Density Electrical Mapping Study of Distinct Neural Processes Underlying Sound Object Recognition and Sound Localization - Leavitt, Victoria M.; Molholm, Sophie; Gomez-Ramirez, Manuel; Foxe, John J. (Frontiers in Integrative Neuroscience, 2011)
Functionally distinct dorsal and ventral auditory pathways for sound localization (where) and sound object recognition (what) have been described in non-human primates. A handful of studies have explored differential processing within these streams in humans, with highly inconsistent findings. Stimuli employed have included simple tones, noise bursts and speech sounds, with simulated left-right spatial manipulations, and in some cases participants were not required to actively discriminate the stimuli. Our contention is that these paradigms were not well suited to dissociating processing within the two streams. Our aim here was to determine how early in processing we could find evidence for dissociable pathways using better titrated what and where task conditions. The use of more compelling tasks should allow us to amplify differential processing within the dorsal and ventral pathways. We employed high-density electrical mapping using a relatively large and environmentally realistic stimulus set (seven animal calls) delivered from seven free-field spatial locations; with stimulus configuration identical across the “where” and “what” tasks. Topographic analysis revealed distinct dorsal and ventral auditory processing networks during the where and what tasks with the earliest point of divergence seen during the N1 component of the auditory evoked response, beginning at approximately 100 ms. While this difference occurred during the N1 timeframe, it was not a simple modulation of N1 amplitude as it displayed a wholly different topographic distribution to that of the N1. Global dissimilarity measures using topographic modulation analysis confirmed that this difference between tasks was driven by a shift in the underlying generator configuration. Minimum norm source reconstruction revealed distinct activations that corresponded well with activity within putative dorsal and ventral auditory structures.